Intradiscal Injection of Autologous Platelet-Rich Plasma Releasate to Treat Discogenic Low Back Pain: A Preliminary Clinical Trial - Akeda, Koji (Asian Spine J, 2017)
STUDY DESIGN: Preliminary clinical trial. PURPOSE: To determine the safety and initial efficacy of intradiscal injection of autologous platelet-rich plasma (PRP) releasate in patients with discogenic low back pain. OVERVIEW OF LITERATURE: PRP, which is comprised of autologous growth factors and cytokines, has been widely used in the clinical setting for tissue regeneration and repair. PRP has been shown in vitro and in vivo to potentially stimulate intervertebral disc matrix metabolism. METHODS: Inclusion criteria for this study included chronic low back pain without leg pain for more than 3 months; one or more lumbar discs (L3/L4 to L5/S1) with evidence of degeneration, as indicated via magnetic resonance imaging (MRI); and at least one symptomatic disc, confirmed using standardized provocative discography. PRP releasate, isolated from clotted PRP, was injected into the center of the nucleus pulposus. Outcome measures included the use of a visual analog scale (VAS) and the Roland-Morris Disability Questionnaire (RDQ), as well as X-ray and MRI (T2-quantification). RESULTS: Data were analyzed from 14 patients (8 men and 6 women; mean age, 33.8 years). The average follow-up period was 10 months. Following treatment, no patient experienced adverse events or significant narrowing of disc height. The mean pain scores before treatment (VAS, 7.5±1.3; RDQ, 12.6±4.1) were significantly decreased at one month, and this was generally sustained throughout the observation period (6 months after treatment: VAS, 3.2±2.4, RDQ; 3.6±4.5 and 12 months: VAS, 2.9±2.8; RDQ, 2.8±3.9; p<0.01, respectively). The mean T2 values did not significantly change after treatment. CONCLUSIONS: We demonstrated that intradiscal injection of autologous PRP releasate in patients with low back pain was safe, with no adverse events observed during follow-up. Future randomized controlled clinical studies should be performed to systematically evaluate the effects of this therapy.